Frequency and Severity of Thrombocytopenia in Neonatal Sepsis - Khan, Abdullah; Iqbal, Amjad; Ali, Syed Abbas; Wakil, Asif; Saeed, Mahnoor; Shah Fahad Ullah (Indus Journal of Bioscience Research, 2025)
Background: Neonatal sepsis is serious infection in first 28 days of life and it can cause many hematological problems. One common problem is thrombocytopenia which increase risk of bleeding and poor outcome. Objective: To determine the frequency and severity of thrombocytopenia in neonates with sepsis. Study Design: Descriptive cross-sectional study. Duration and Place of Study: Conducted from 5 April 2024 to 5 October 2024 at Neonatal Intensive Care Unit, Combined Military Hospital Abbottabad. Methodology: A total of 136 culture positive septic neonates aged ≤28 days were included by calculated sample size. Demographic and clinical data were recorded. Thrombocytopenia was noted. Data was analyzed by Statistical Package for Social Sciences version 26. Mean ± standard deviation was calculated for quantitative variables. Chi-square test was applied after stratification and p ≤0.05 was taken significant. Results: Mean age was 14.49 ± 7.99 days and mean weight 2.97 ± 0.51 kg. Thrombocytopenia was found in 85 (62.50%) neonates. Among them, mild was 23 (27.10%), moderate 31 (36.50%) and severe 31 (36.50%). Age >14 days showed higher thrombocytopenia 49 (71.0%) compared to ≤14 days 36 (53.7%) (p=0.037). Gender, mode of delivery and feeding type had no significant association (p>0.05). Conclusion: Thrombocytopenia is common in neonatal sepsis and most cases are moderate to severe. Increasing age is significant associated factor.